Intended and Unintended Consequences of a Community-Based Fresh Fruit and Vegetable Dietary Intervention on the Flathead Reservation of the Confederated Salish and Kootenai Tribes - Ahmed, Selena; Dupuis, Virgil; Tyron, Michael; Running Crane, MaryAnn; Garvin, Teresa; Pierre, Michael; Byker Shanks, Carmen (Frontiers in Public Health, 2020)
Tribal communities in the United States face disparities to accessing healthy foods including high-quality produce. A six-week fresh fruit and vegetable (FV) dietary intervention, Eat Fresh, was co-designed with a Community Advisory Board of local food and nutrition stakeholders on the Flathead Reservation of the Confederated Salish and Kootenai Tribes in Montana. Eat Fresh was implemented as a pilot study with low-income participants (n=19) enrolled in the Food Distribution Program on Indian Reservations towards improving dietary quality and perceptions of wellbeing. We evaluated Eat Fresh at pre- and post-intervention on the basis on food procurement practices, dietary quality using the Healthy Eating Index (HEI), Body Mass Index (BMI), blood pressure, and participant perceptions of health. Participants reported consuming a greater number of types of FVs daily during the intervention (p < 0.005 for fruits and p > 0.19 for vegetables). Overall, participants found Eat Fresh moderately challenging to adhere to with the main barriers being access to ingredients in recipes (39.51% of responses), time constraints to cook (35.80%), and lack of financial resources (33.33%). Dietary quality improved during the intervention from a mean HEI score of 48.82 ( 11.88) out of 100 to 56.92 ( 11.88; (p > 0.12). HEI scores for fruit consumption significantly increased (p < 0.05) from 1.69 (out of 5 points) during the pre-intervention to 2.96 during the post-intervention. BMI and blood pressure increased for several participants, highlighting an unintended consequence. Most participants responded that FV consumption made them feel either very good (51.16%) or good about their health (43.02%) with the majority (83%) perceiving an improvement in energy. Findings of this pilot study highlight both intended and unintended consequences of a dietary intervention that provide lessons in co-designing community-based programs.